PERENCANAAN PEMBUATAN PAGAR PENAHAN JET BLAST PADA APRON TERHADAP GEDUNG TOWER DI BANDAR UDARA SILAMPARI LUBUKLINGGAU - Pandu Aji Kusumo; Ranatika Purwayudhaningsari; Safitri Nur Wulandari (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Silampari Airport is a class III airport managed by the UPBU of the Directorate General of Civil Aviation, located in Lubuklinggau City, South Sumatra Province. This airport has an apron area of ​​130 m x 100 m using flexible pavement. At Silampari Airport there is one factor that does not meet the criteria, namely protection against jet blasts. Jet Blast causes vibrations on the 1st floor of the tower building. The maximum speed generated from the jet blast at Silampari Lubuklinggau Airport is 162 km/hour or 45 m/s. The maximum wind speed from jet blast pursuant to Government Decree Number 39 of 2015 is 100 km/hour or 27.7 m/s, so that the speed of the jet blast is 162 km/hour > 100 km/hour, it is necessary to build a jet blast retaining fence to reduce the effects of jet blasts from the largest aircraft at Silampari Lubuklinggau Airport, namely the Airbus A320-200. In this final project, we plan to make a jet blast retaining fence using a steel structure and the required budget plan (RAB). The reference used in this final project refers to national and international regulations and has been determined by the International Civil Aviation Organization (ICAO), in determining the jet blast retaining fence model is BDI (Blast Deflector, Inc.) The method used in determining the steel profile used to determine the budget plan used the unit price analysis guidelines issued by the Directorate General of Civil Aviation. Based on research on the manufacture of jet blast retaining fences that have been carried out at Silampari Airport, Lubuklinggau, the steel material used is BJ41 quality with angled steel profile of 100 x 100 x 7, hollow steel profile of 100 x 100 x 7 with a base structure of reinforced concrete plate K350 and reinforcement used is D13. Meanwhile, the RAB required in the manufacture of a jet blast retaining fence with dimensions of 8 meters long, 9 meters wide, and 10 meters high is IDR 303,270.00.00 with a VAT fee of 10%.